Teaching and learning of biosciences in a digital world: challenges and effective teaching strategies during and after Covid-19 pandemic - Cheema, Manraj Singh; Othman, Zulkefley; Sarchio, Seri Narti Edayu; Syed Alwi, Sharifah Sakinah; Md Hashim, Nur Fariesha; Liew, Chin Teng (Universiti Putra Malaysia, 2022)
The global pandemic of COVID-19 has had a huge influence on bioscience education in which digital technology and transformation has gained momentum and this pattern appears to be set to persist for the foreseeable future. Adopting new technology and changing biosciences education models, processes, and procedures has posed challenges to all stakeholders within the ecosystem. Aside from the move to online or distance learning, bioscience courses in higher education also necessitate the development of critical practical skills, which is yet to be fully addressed in digital platform context. This article examines the challenges and issues that biosciences education faces, as well as the tactics, methodologies, and alternatives that have been employed in the present pandemic context to reform biosciences education to enhance its resiliency and sustainability. This article also defines effective teaching criteria in biosciences education and considers whether higher education institutions can use virtual learning to offer the newest bioscience skills and knowledge to be future-proof and job-ready.